Exposure to ambient PM2.5 constituents and semen quality in a retrospective cohort study: Windows of susceptibility and modification by greenness - Ling Yang; Ziwen Hu; Xiyan Wu; Xinghua Yang; Linfei Dou; Yanling Shu; Mingyang Wu (International Journal of Hygiene and Environmental Health, 2026)

Influence of different cooling treatments on micro-cracking behaviour of marble: Insight from grain-based modelling - Fan Bu; Jun Peng; Linfei Wang; Bibo Dai; Junxing Zhu; Xiaogang Wu (Computers and Geotechnics, 2026)

Associations between early life exposure to persistent organic pollutants and mitochondrial DNA copy number in infants - Xinghua Yang; Shiting Xiang; Linfei Dou; Xirennayi Abudurexiti; Xiongfeng Pan; Jun Qiu; Mingyang Wu (Environmental Pollution, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Zoning for synergistic reduction of pollution and carbon emissions in the Beijing-Tianjin-Hebei and its surrounding areas based on environmental justice principles - Juan Du; Xiangwei Ren; Linfei Wu (Science of The Total Environment, 2025)

Contribution of deep organic fluids to uranium mineralization in Cretaceous sandstones of the southwestern Ordos Basin, China - Linfei Qiu; Ziying Li; Feng He; Zhenqian Wu; Kunpeng Liu; Liang Zhang; Ning Mao; Tingting Wang; Lu Wang (Hydrogeology Journal, 2025)
In recent years, significant advancements have been achieved in uranium (U) prospecting within the Lower Cretaceous strata of the southwestern Ordos Basin, China. U deposits have been unearthed in Zhenyuan and Pengyang County, predominantly found within the Cretaceous sandstones of the Luohe and Huanhe formations. These ore-bearing strata primarily originate from arid environments, characterized by a deficiency of organic matter (OM). This deposit type manifests within lenticular, gray sandstone interbedded within red sandstone. Its genesis markedly diverges from oxidation-reduction sandstone-type U deposits, yet systematic studies on the properties of ore-forming fluids, particularly their sources and contributions to U mineralization, remain lacking. Core observations were conducted, and representative samples were collected for laboratory analysis. This study discerns the characteristics of ore-forming fluids within the U-bearing sandstone and deliberates the source of these fluids and their impact on U mineralization. Results indicate an abundance of flow-patterned , OM-rich U ores, derived from the deep mudstone rocks of the Yanchang Formation. The ore-forming fluids, characterized as OM-rich and low-temperature (130 to 180°C) hydrothermal fluids, originate from fluid discharge within the source rocks. Subsequently, ore-forming materials dissolve within these OM-rich fluids and migrate towards the oxidized sandstone in shallower regions. Significant changes in temperature and oxygen fugacity lead to fluid differentiation or cracking, facilitating U precipitation into U ores. The characteristics of Cretaceous U mineralization in the study area are consistent with the exudative model of sandstone-type U metallogenesis.

Synthesizing furfuryl ethers with high selectivity by reductive etherification of furfural on the bifunctional catalysts consisting of Ni3P and nano-ZSM-5 - Nali Chen; Linfei Xiao; Wei Wu (Sustainable Chemistry and Pharmacy, 2025)

Sustainable strategy for removing Ag impurities from crude gold via a vacuum distillation process to produce a 4N gold product - Weihuang Wu; Yichao Yang; Hangxin Qiu; Linfei He; Guozheng Zha; Wenlong Jiang; Baoqiang Xu; Bin Yang; Xu Cao (Journal of Cleaner Production, 2025)

Research on the influence mechanism of multiple network interactive embedding on green dual innovation synergy in manufacturing enterprises - Xiangwei Ren; Linfei Wu; Juan Du (Environment, Development and Sustainability, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Continuous-flow reductive etherification of furfural over CuAlOx catalyst combined with HZSM-5-Al2O3 composite - Alexey L. Nuzhdin; Yazhou Wang; Evgeniya N. Vlasova; Marina V. Bukhtiyarova; Irina G. Danilova; Svetlana A. Yashnik; Alyona A. Pochtar; Linfei Xiao; Wei Wu; Galina A. Bukhtiyarova (Fuel, 2024)

The effects of growth modifiers on the catalytic performance of hierarchical Pd/ZSM-23 bifunctional catalysts for n-hexadecane hydroisomerization - Jiazheng Sun; Shuxiang Xiong; Hailong Lin; Qiong Wu; Linfei Xiao; Zhenni Liu; Xiujie Li; Wei Wang; Wei Wu (Fuel, 2023)

Cadmium exposure is associated with decreased muscle strength in middle-aged and older adults - Mingyang Wu; Linfei Dou; Aisimila Abudoula; Yanling Shu; Youjie Wang (Environmental Science and Pollution Research, 2023)

Design of MDOF structure with damping enhanced inerter systems - Ruifu Zhang; Minjun Wu; Chao Pan; Chao Wang; Linfei Hao (Bulletin of Earthquake Engineering, 2023)

Global characteristics and trends of research on industrial structure and carbon emissions: a bibliometric analysis - Liwen Sun; Linfei Wu; Peixiao Qi (Environmental Science and Pollution Research, 2020)

Migration of impurity level reflected in the electrical conductivity variation for natural pyrite at high temperature and high pressure - Kaixiang Liu; Lidong Dai; Heping Li; Haiying Hu; Lei Wu; Yukai Zhuang; Chang Pu; Linfei Yang (Physics and Chemistry of Minerals, 2018)

The effect of l-carnosine on the circadian resetting of clock genes in the heart of rats - Tao Wu; Yanlai Tao; Fai Tsang; Keiichi Abe; Liang Xu; Qianru Jiang; Linfei Xu; Haoxuan Fu; Zhengwei Fu (Molecular Biology Reports, 2015)